2018
DOI: 10.1371/journal.pone.0196279
|View full text |Cite
|
Sign up to set email alerts
|

Association of Raynaud’s phenomenon with a polymorphism in the NOS1 gene

Abstract: BackgroundRaynaud’s phenomenon (RP) describes the phenomenon of recurrent vasospasm of digital arteries, associated with skin colour changes: pallor, cyanosis and erythema. Twin studies have indicated a genetic predisposition for RP; however, the precise aetiology of RP remains unknown. It is thought that genetic variation in temperature-responsive or vasospastic genes might underlie RP so performed a candidate gene study in a large, population based sample. We assessed the association between RP and single nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 18 publications
0
6
0
1
Order By: Relevance
“…mechanistic and therapeutic interest, Munir et al reported that RP is associated with a polymorphism in the NOS1 gene 14. …”
mentioning
confidence: 99%
“…mechanistic and therapeutic interest, Munir et al reported that RP is associated with a polymorphism in the NOS1 gene 14. …”
mentioning
confidence: 99%
“…In 2000, Susol E. et al conducted a genome-wide screen to identify chromosomal regions containing genes conferring susceptibility to RP, and identified three potential candidate genes: the beta subunit of the muscle acetylcholine receptor and the serotonin 1B and 1E receptors by a two-stage screening process [21]. Crispin JC et al assessed the association between RP and single nucleotide polymorphisms (SNPs) in temperature-responsive or vasospastic genes and found that RP was associated with variation in gene NOS1 [22]. Additionally, it has been suggested that MTHFR mutation is more frequently found in patients with RP, which confirms genetic predisposition may play a key role in the pathogenesis of RP [23].What's more, geographical factors may also lead to differences, because a colder climate may promote the development of RP [24].…”
Section: Discussionmentioning
confidence: 99%
“…Carriers of at least one C allele at the polymorphic site CALCA T-692C showed increased risk for hypertension [ 114 ]. The CALCB gene polymorphism rs16930880 was also confirmed to be associated with vasospasm of Reynolds phenomenon [ 115 ]. As the mice grew older, the aging lumbar dorsal root ganglia (DRGs) showed peripheral sensitization, inflammatory reaction, and high expression of neurotransmitter CALCA mRNA [ 116 ].…”
Section: Cgrp and Nervous System Diseasesmentioning
confidence: 99%